Post-ecorestoration impact on fish and shellfishbiodiversity in Chilika lake - Mohanty, Rajeeb K; Mohanty, S K; Mohapatra, A; Bhatta, K S; Pattnaik, A K (Indian Journal of Fisheries, 2011)
The hydrological intervention in Chilika lake during the year 2000, restored theunique coastal wetland ecosystem, which was under severe threat due tocontinued natural changes and unabated anthropogenic pressure. Fish yieldand biodiversity of the lake, has spectacularly been enhanced due to the eco-restoration measures particularly, after opening of the new mouth at a shorterdistance of 11 km from the lake proper. Apart from significant increase in theaverage yield of fish and shellfish during post-mouth period (2000-01 to 2003-04) by 431.78% and 1198.11% respectively, in comparison to pre-mouth period(1996-97 to 1999-2000), there has been significant improvement in fishbiodiversity with new records of 56 species, totaling to 268 fish species, 28 prawnand 35 crab species. Two species of Indian spiny lobsters (Panulirus ornatusand Panulirus polyphagus) have been collected from the lake for the first timeduring 2003. Total records of species of fish and shellfish (277) during pre-restoration phase increased to 333 number during post-restoration phaseindicating 20.22% increase. In total, 221 species (187 fish, 18 prawns and shrimps,2 lobsters and 14 crabs) were collected during inventorisation survey, whichindicated that migratory species constitute 74.55% and marine-brackish fishfauna constitute 72.73%. Outer channel sector exhibited the maximum speciesrichness (62.44%) and southern sector exhibited the minimum (14.93%) duringsummer and monsoon respectively. Greater contribution by migratory speciesof fish, prawns and crabs to the bulk of catches establishes that the recruitmentof juveniles from the sea and maintenance of estuarine character of the Chilika ecosystem are the key factors for enhancement of fisheries resources.